2003
DOI: 10.1046/j.1365-2532.20.s1.4.x
|View full text |Cite
|
Sign up to set email alerts
|

A Delphi study to determine nursing research priorities in the North Glasgow University Hospitals NHS Trust and the corresponding evidence base

Abstract: The aims of the study are to identify and prioritize research questions of importance to nurses in North Glasgow University Hospitals NHS Trust and to investigate and describe the existing evidence base for the highest priority questions identified. The consensus method known as the Delphi technique was used. Systematic searching of the literature for each question identified from the research priorities enabled the existing evidence base to be characterized. The following priorities were identified as the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Using a mean value in collapsing the responses has been used in numerous Delphi studies with ranking the mean value considered as a typical method in prioritization. 18…”
Section: Discussionmentioning
confidence: 99%
“…Using a mean value in collapsing the responses has been used in numerous Delphi studies with ranking the mean value considered as a typical method in prioritization. 18…”
Section: Discussionmentioning
confidence: 99%
“…In phase II, the content and face validity was done with the Delphi technique. Delphi technique has also been used by Kirkwood et al 10 to determine nursing research priorities in the North Glasgow University Hospitals. They found that three Delphi rounds were sufficient to reach consensus.…”
Section: Discussionmentioning
confidence: 99%
“…The Delphi method is widely used and accepted for consensus building on a specific topic (Hsu & Sandford, ). Nurses have used the Delphi method to ascertain priorities or determine developments for research, education, and clinical practice (Kirkwood, Wales, & Wilson, ). The Delphi method was selected for this study because it maintains subject anonymity and minimizes bias or coercion due to influence of individual members in group discussion (Hsu & Sandford, ).…”
Section: Methodsmentioning
confidence: 99%